2017
DOI: 10.1080/00223891.2017.1281286
|View full text |Cite
|
Sign up to set email alerts
|

The Thorny Relation Between Measurement Quality and Fit Index Cutoffs in Latent Variable Models

Abstract: Latent variable modeling is a popular and flexible statistical framework. Concomitant with fitting latent variable models is assessment of how well the theoretical model fits the observed data. Although firm cutoffs for these fit indexes are often cited, recent statistical proofs and simulations have shown that these fit indexes are highly susceptible to measurement quality. For instance, a root mean square error of approximation (RMSEA) value of 0.06 (conventionally thought to indicate good fit) can actually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
225
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(238 citation statements)
references
References 39 publications
6
225
1
6
Order By: Relevance
“…For the Spanish and Dutch translated versions of the SELAQ, the alternative fit indices do show the model fit to be acceptable. Although the RMSEA is high for the Spanish predicted expectation scale, the measurement quality is good and this is associated with the RMSEA functioning (McNeish et al, ). Thus, on the basis of these findings, it does support the use of the SELAQ to measure student expectations within these contexts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the Spanish and Dutch translated versions of the SELAQ, the alternative fit indices do show the model fit to be acceptable. Although the RMSEA is high for the Spanish predicted expectation scale, the measurement quality is good and this is associated with the RMSEA functioning (McNeish et al, ). Thus, on the basis of these findings, it does support the use of the SELAQ to measure student expectations within these contexts.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in the work of Xia (), it is inappropriate to generalize the Hu and Bentler criteria to occasions when the ULSMV estimator is used due to its dependency upon thresholds. In addition, the simulation study of McNeish, An, and Hancock () has shown these alternative fit indices (i.e., CFI and RMSEA) to be affected by the measurement quality of the model. Specifically, increased standardized factor loadings result in model fit indices that would be indicative of poor fit (Hancock & Mueller, ).…”
Section: Methodsmentioning
confidence: 99%
“…RMSEA value was just within the acceptable cutoff (.08) probably due to the large factor loadings size. Recent simulation studies have shown that in the presence of factor loadings above .70 the value of RMSEA tends to increase (McNeish, An, & Hancock, 2017;Savalei, 2012). Correlation between factors was moderate (r = .60).…”
Section: Scq-shst Validationmentioning
confidence: 95%
“…SRMR or the RMSEA). Fit indices can be affected by a range of model and data properties including sample size, measurement quality, estimation method, misspecification and more (Fan, Thompson, & Wang, 1999;McNeish, An, & Hancock, 2017;Moshagen & Erdfelder, 2016). Competing models can be compared using traditional likelihood ratio test if models are nested (Neale, 2000), or specialized version of the LRT for non-nested models (Merkle, You, & Preacher, 2016).…”
Section: Model Fit Model Estimation and Model Comparisonmentioning
confidence: 99%